Drawing with Mark. A day with the dinosaurs ; Reach for the stars. [videorecording (DVD)] (Shelter Island, 2013)
Mark Marderosian visits the Museum of Science in Boston where he introduces his viewers to dinosaurs and how they lived. Viewers then learn how to draw a Tyrannosaurus Rex and a Pterodactyl. On a second visit to the museum, Mark and the 'Angels from the Attic' learn about outer space, planets, and stars. The drawing lessons feature the planet Saturn and a friendly astronaut on the moon.